A Systematic Approach to Solving Problems in Structure Analysis - Mohd Nor, Rehan (1988)
An investigation of students' unsuccessful attempts to solve problems in structure analysis, even though they possessed all the prerequisite knowledge, is described. The proposed teaching strategies given to these students to help them develop confidence and skills in problem-solving and the evaluation of these strategies are discussed.